Pengurutan nilai siswa menggunakan algoritma bubble sort - Andriansyah, Rafiq Alhariri (Maliki Interdisciplinary Journal, 2025)
In order to calculate the final grade that can be used as an assessment of student achievement, a lot of work must be done to create tests for each student. Sorting data in this situation is usually necessary, especially in educational institutions such as schools. The process of sorting student success data in schools usually involves a number of criteria that have been set by the school and takes a long time because of the large number of students and classes in a school, especially in private schools. Algorithms or other techniques that can help the process of assessing student achievement can also be used for this when sorting data. One of the data sorting techniques is the bubble sort algorithm. To directly determine the desired value provisions based on the required criteria, this algorithm can compare data from highest to lowest or vice versa. Sorting student success data before being printed on student report cards can be done more easily and lightly for teachers by using the Bubble Sort Algorithm. When making a final report on student success evaluation, teachers can use the output of the algorithm as a benchmark.